Shifting Landscape of Rural Transformation in Bangladesh: Exploring the Interplay of Non‐Farm GDP, Infrastructure and Education - Subrata Saha; Mohammad Jahangir Alam; Al Amin Al Abbasi; Ismat Ara Begum; Maria Fay Rola‐Rubzen (Asia & the Pacific Policy Studies)
ABSTRACT Rural transformation is critical for supporting inclusive economic development. This study assessed the effect of infrastructure and education on the process of rural transformation in Bangladesh using data from four waves of Household Income and Expenditure Surveys between 2000 and 2016. This study employed the Fixed Effects Model, Moment‐Quantile Regression with Fixed Effects Model, and Feasible Generalised Least Squares for checking robustness. The results show that infrastructure and education positively affect rural transformation. The expansion of small‐scale farms, improved healthcare accessibility, and land rental arrangements are key factors that facilitate transformation, whereas the rise of large‐scale farming has a negative impact. Policy recommendations highlight investment in infrastructure and educational access, such as universal primary education, to enhance transformation. It also suggests encouraging land rentals, improving healthcare services, and supporting small‐scale farming while addressing the drawbacks of large‐scale farming to strengthen economic convergence between rural and urban areas.